Is China unique?: exploring the behaviour of Chinese and European firms in the Cameroonian logging sector - Cerutti, P.O.; Assembe-Mvondo, Samuel; German, L.; Putzel, L. (2011)
China’s growing presence in Africa’s extractive industries has been the subject of much debate in recent years, reflecting concerns about both environmental sustainability and the governance of resource wealth for long-term benefit. In Cameroon, since 2000 the largest timber concession in the country has been held by a Chinese company. This provides an opportunity to take a deeper look at corporate practices in the extractive industry and explore the extent to which corporate behaviour varies between Chinese and non-Chinese companies. Through a general analysis of Cameroonian timber production and trade, and a detailed analysis of two European companies (one FSC-certified) and one Chinese company (without FSC certification), this paper assesses the effects of Chinese capital and China-related trade on rural livelihoods and forest condition in the Cameroonian forestry sector. Our findings suggest that while the Chinese market shapes the trade patterns and management activities of logging companies, it does so irrespective of the companies’ nationality. Also, findings suggest that nationality of firms has a weak influence on the impacts on local livelihoods around the sampled logging concessions in Cameroon.